2018
DOI: 10.1080/14767058.2018.1474870
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and cosmetic outcome in a randomized study of cesarean skin closure

Abstract: Satisfaction with the closure method, satisfaction with the scar's appearance, and patient and physician assessments of scar cosmesis were all superior in those closed with suture. These results further support the use of sutures for cesarean skin closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…71 Additionally, women also have improved preference and experience scores with suture closure. 72 One caveat is that the only difference is in wound separation; in many trials, staples were removed <4 days after surgery. Similarly, in a recent trial of obese women only, although there were no clinical differences, more women would choose suture for a future surgery.…”
Section: Repair Of Incisionmentioning
confidence: 99%
“…71 Additionally, women also have improved preference and experience scores with suture closure. 72 One caveat is that the only difference is in wound separation; in many trials, staples were removed <4 days after surgery. Similarly, in a recent trial of obese women only, although there were no clinical differences, more women would choose suture for a future surgery.…”
Section: Repair Of Incisionmentioning
confidence: 99%
“…In 2018, Fleisher et al [26] evaluated patient satisfaction and patient and physician assessment of scar appearance after Cesarean skin closure with suture versus staples. The scores were assessed at a median of 46 days postoperatively.…”
Section: All Participants Enrolled In This Clinical Investigationmentioning
confidence: 99%
“…Yang et al [24] concluded that intradermal vertical mattress sutures are superior cosmetically to subcuticular sutures. Greater patient and physician satisfaction and better cosmetic outcomes were observed with the suture closure method than with the staple closure method [25].…”
Section: Discussionmentioning
confidence: 98%